Advances in nanocarriers as drug delivery systems in chagas disease - Quezada, Christian Quijia [UNESP]; Azevedo, Clênia S.; Charneau, Sébastien; Santana, Jaime M.; Chorilli, Marlus [UNESP]; Carneiro, Marcella B.; Bastos, Izabela Marques Dourado (Taylor & Francis, 2019)
Chagas disease is one of the most important public health problems in Latin America due to its high mortality and morbidity levels. There is no effective treatment for this disease since drugs are usually toxic with low bioavailability. Serious efforts to achieve disease control and eventual eradication have been unsuccessful to date, emphasizing the need for rapid diagnosis, drug development, and a reliable vaccine. Novel systems for drug and vaccine administration based on nanocarriers represent a promising avenue for Chagas disease treatment. Nanoparticulate systems can reduce toxicity, and increase the efﬁcacy and bioavailability of active compounds by prolonging release, and therefore improve the therapeutic index. Moreover, nanoparticles are able to interact with the host’s immune system, modulating the immune response to favour the elimination of pathogenic microorganisms. In addition, new advances in diagnostic assays, such as nanobiosensors, are beneﬁcial in that they enable precise identiﬁcation of the pathogen. In this review, we provide an overview of the strategies and nanocarrier-based delivery systems for antichagasic agents, such as liposomes, micelles, nanoemulsions, polymeric and non-polymeric nanoparticles. We address recent progress, with a particular focus on the advances of nanovaccines and nanodiagnostics, exploring new perspectives on Chagas disease treatment.
Keywords: Delivery systems; Nanobiosensors; Nanodiagnostics; Nanoparticle systems; Nanovaccine